Hip injuries in tennis - Byrd, J. W. T. (Medicine and Science in Tennis, 2003)
An increasing number of hip joint injuries have been observed in professional tennis. There are three reasons for this. First, there is a growing awareness of the existence of these injuries, second is the improved diagnostic capabilities for assessing these problems, and third is the changing pattern of play in elite tennis. Author discusses the importance of arthroscopy for diagnosis and therapy. He summarizes: The arthroscope has been instrumental in recognising, understanding, diagnosing, and treating hip joint pathology in athletes. We are beginning to appreciate that these injuries, like so many others, occur as a consequence of athletes pushing their bodies to the physiologic limits where breakdown occurs. We must now use this knowledge to focus on injury prevention through aspects of conditioning, training, and technique. In turn, this will undoubtedly expand the envelope, stretch the physiologic barriers, and further improve the performance of these remarkably gifted athletes.